PERAMPANEL EFFECTIVENESS IN THE TREATMENT OF REFRACTERY PARTIAL ONSET EPILEPSY WITH OR WITHOUT SECONDARY GENERALIZATION: PHARMACOECONOMIC ANALYSIS FOR THE RUSSIAN FEDERATION HEALTH CARE SYSTEM - N. K. Mazina; I. V. Sheshunov; P. V. Мazin; Yu. V. Kislitsin; E. M. Markova (IRBIS LLC, 2017)
Perampanel (PER) is a novel drug for treatment of refractory partial epilepsy in patients≥12 y.o. with proven efficacy and safety. PER is registered and may also be used successfully as adjunctive treatment in therapy of primary generalized tonic-clonic seizures (PGTCS).Objective. To determine the effectiveness of perampanel and it`s clinical stability in patients at different dosing regimens, and evaluate the cost of treatment with perampanel in the Russian Health Care system.Materials and Methods. Results of open multicenter controlled randomized (phase III) international clinical trials in patients over 12 years of age were used. Modeling of the direct costs was based on (i) the probable treatment outcomes: i.e., no clinical effect, treatment cessation due to adverse events, seizures reduction of 50% and more, complete seizure termination, (ii) the expected number of the above outcomes all overRussia, and (iii) the inflation risks in the period until 2020.Results. The comparison of different clinical studies on adjunctive perampanel therapy in refractery partial epilepsy with or without secondary generalization as well as in primary generalized tonic-clonic seizures, reveales that the optimal daily dose of perampanel is 8 mg.Conclusion. Direct costs modeling was performed to estimate annual expenses (per patient) of the adjunctive perampanel therapy. When recalculated for all patients with refractory partial epilepsy and for all patients with PGTCS inRussia, the results indicate that the introduction of perampanel may reduce the costs by more than 40% (up to 4-7 bln. rubles) annually until 2020.